Case report: Emphysematous pyelonephritis associated with kidney allograft abscess formation - Abu Jawdeh, Bassam G.; Nguyen, Michelle C.; Ryan, Margaret S.; Vikram, Holenarasipur R. (Frontiers in Medicine, 2022)
Emphysematous pyelonephritis (EPN) is a severe, acute necrotizing infection that is defined by the presence of gas in the kidney parenchyma. Multiple case reports have described the radiologic findings and clinical course of EPN. Herein, we report on EPN including the histopathologic findings in a kidney transplant recipient. Our patient presented with EPN complicated by multiorgan failure and was successfully managed with transplant nephrectomy.